Green Hotel Design Model: Integration of Balinese Architecture and Passive Cooling Systems - Gunardhy, Marthin; Putra, I Dewa Gede Agung Diasana; Dwijendra, Ngakan Ketut Acwin; Adhika, I Made (ASTONJADRO, 2026)
The hospitality sector in Bali, a major contributor to the island's tourism economy, faces significant challenges in energy consumption, particularly due to reliance on air conditioning systems for thermal comfort. These systems account for over 60% of the total energy use in star-rated hotels. In contrast, traditional Balinese architecture has long utilized passive design strategies—such as cross ventilation, thermal-insulative local materials, and site planning in accordance with Tri Hita Karana philosophy—to achieve indoor comfort without active cooling. This research proposes a green building design model that integrates traditional Balinese architectural elements with modern passive cooling technologies. The study employs a mixed-methods approach: qualitative data were obtained from interviews with architects, hotel managers, and users; quantitative data were collected through energy consumption measurements (kWh/m²/year) before and after passive design interventions. Four hotel areas—Sanur, Kuta, Ubud, and Nusa Dua—were selected as case studies. Results show that cross-ventilation and traditional spatial arrangements can reduce indoor temperatures by an average of 3.2°C, lowering energy use by 20–30%. Integration with reflective coatings, thermal insulation, and double-glazed windows further improves energy performance, achieving up to 32.4% reduction. This model demonstrates strong acceptance by users and is contextually adaptive to coastal microclimates. The research contributes a validated, culturally grounded green design framework, bridging local wisdom with sustainable development imperatives in tropical tourism zones.